Peran Konseling Islam dalam Menanamkan Moderasi Beragama di Kantor Urusan Agama Kecamatan Medan Perjuangan - Putri Rizkyana Silalahi; Misrah Misrah (Faculty of Social Science, Universitas Negeri Padang, 2023)
This study aims to determine the role of Islamic counseling in instilling religious moderation in the Medan Perjuangan District Office of Religious Affairs. This research is a type of field research (field study). The method used is qualitative. Data collection was carried out by interview, observation, and documentation methods. The subject of this research is the Islamic Extension Officer of the Medan Perjuangan District Office. The collected data were then analyzed using Miles and Hubberman's theory which included data reduction, data presentation, and drawing conclusions. The results of the study show that 1. Religious educators play an important role in helping people understand and instill religious values and religious moderation through the study of religious knowledge and understanding and by continuing to provide religious advice to help people understand religious moderation through scientific research, understanding religion, sustainable religious development, teaching moral principles and upholding humanity by applying the principles of justice, balance and tolerance. 2. Islamic counseling has a role as a service and facility in providing assistance to the community to provide an understanding of religion and religious moderation, with individual counseling in solving problems. 3. In the form of joint sports activities, joint karaoke and carrying out social activities in the form of mutual cooperation activities, socialization and seminars in the form of discussion forums where discussions with institutions.